PELATIHAN PEMBUATAN BLOG SEBAGAI MEDIA DALAM PEMBELAJARAN SMK - Salim, Salim; Ikman, Ikman; Suhar, Suhar; Kodirun, Kodirun; Pabunga, Dorce Banne; Saputra, Hendra Nelva (Universitas PGRI Yogyakarta, 2020)
The purpose of this service is to improve the teachers' pedagogical skills in the field of medicine and there is increased learning quality by using a blog. This devotion is necessary to increase the teacher's insight into the pedagogical competence of ict-based learning. This has supported a number of studies which show that blogs can become learning media that can facilitate the process of interaction between teachers and students. The methods used were those of speech, question-and-answer, and simulation. The success indicator of this devotion activity includes: (1) participants' positive response to the blog development training in SMK learning, and (2) the product a trainee produces is a blog that can be used in learning. The result of this activity suggests that (1) teachers already have the knowledge to create a blog for learning purposes, (2) teachers already have the learning media utilizing the blog application, and (3) teachers have a knowledge of designing and creating blog content as a learning medium.